2018
DOI: 10.1038/s41598-018-33155-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dimensions of biodiversity drive human interest in tide pool communities

Abstract: Activities involving observation of wild organisms (e.g. wildlife watching, tidepooling) can provide recreational and learning opportunities, with biologically diverse animal assemblages expected to be more stimulating to humans. In turn, more diverse communities may enhance human interest and facilitate provisioning of cultural services. However, no experimental tests of this biodiversity-interest hypothesis exist to date. We therefore investigated the effects of different dimensions of animal biodiversity (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 93 publications
(94 reference statements)
1
15
0
Order By: Relevance
“…Overall, our study provides experimental evidence that the relationship between diversity and human preference is more complex that previously stated (e.g. [10,[11][12][13]). While all previous studies found a positive effect of diversity on human preferences, we find a saturating effect of species' richness, a net negative effect of species' abundances and no effect of functional diversity.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Overall, our study provides experimental evidence that the relationship between diversity and human preference is more complex that previously stated (e.g. [10,[11][12][13]). While all previous studies found a positive effect of diversity on human preferences, we find a saturating effect of species' richness, a net negative effect of species' abundances and no effect of functional diversity.…”
Section: Discussionsupporting
confidence: 69%
“…[31]). As shown in Tribot et al [9] and Fairchild et al [13], the characteristics that trigger positive responses seem to be bright and contrasted colour patterns (i.e. Pygoplites diacanthus).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“… Gittins et al (2021) showed wellbeing gains from time spent in the woods (Actif Woods Wales program) for people with a range of health and social vulnerabilities. Fairchild et al (2018) examined how greater habitat diversity can play a role in enhancing human interest in conservation, facilitating educational and recreational benefits. This working area focuses on identifying, within the context of both United Kingdom and Brazil, socioeconomic barriers to this human-nature connection which often lead to unequal access to outdoor spaces.…”
Section: Working Across Sectors and Disciplinesmentioning
confidence: 99%
“…Although various wider contextual factors may influence the biological communities that can survive on structures (e.g. disturbance [ 31 ] and water quality [ 32 ]), experimental evidence suggests interventions that add structural complexity can increase the abundance and diversity of intertidal species [ 27 ] that in turn may increase their aesthetic value [ 33 ]. There may be scenarios where a lack of colonization is desirable on coastal structures when ‘fouling’, particularly by non-native species, is considered problematic [ 34 ].…”
Section: Introductionmentioning
confidence: 99%